The study of used of ceramic industrial waste as replacement material of fine aggregate in concrete mix - Mohd Fodzi, Muhammad Haikal; Ahmad Jeni, Mohamad Luthfi (Penerbit Uthm, 2018)
Concrete is a global material that underwrites commercial well-being and social development. These days, there two commonly used structural materials: concrete and steel [1]. Concrete which contains waste products as aggregate is called ‘Green’ concrete. Use of hazardous waste in concrete-making will lead to green environment and sustainable concrete technology and so such concrete can also be called as ‘Green’ concrete. Concrete are mostly used in construction engineering field because the used of the material are economics and have higher strength, durability and availability of raw materials. For this research, the concrete have been modified by replaced the fine aggregate with Ceramic Industrial Waste (CIW) in concrete mix.